2016
DOI: 10.1002/dev.21483
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory sinus arrhythmia moderates the impact of maternal prenatal anxiety on infant negative affectivity

Abstract: Maternal prenatal anxiety is associated with infants’ temperamental negative affectivity (NA), but it is unclear to what extent children vary in their susceptibility to prenatal influences. We tested a hypothesis that infants’ respiratory sinus arrhythmia (RSA), an index of parasympathetic vagal tone and a potential marker of differential susceptibility to environmental influences, moderates the effects of maternal prenatal anxiety on the development of infant NA. Prenatal anxiety was assessed during the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 69 publications
4
28
0
Order By: Relevance
“…Prenatal stress influenced RSA reactivity over time with infants whose mothers reported high prenatal stress, demonstrating persistent RSA suppression following removal of the stressor, consistent with previous literature. 2,4 Clear sex effects were demonstrated in relation to prenatal stress, consistent with the frequently observed relation between prenatal anxiety and infant outcomes, including RSA. 2 We extend this work and demonstrate a unique effect of maternal ACEs on infant RSA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Prenatal stress influenced RSA reactivity over time with infants whose mothers reported high prenatal stress, demonstrating persistent RSA suppression following removal of the stressor, consistent with previous literature. 2,4 Clear sex effects were demonstrated in relation to prenatal stress, consistent with the frequently observed relation between prenatal anxiety and infant outcomes, including RSA. 2 We extend this work and demonstrate a unique effect of maternal ACEs on infant RSA.…”
Section: Discussionsupporting
confidence: 85%
“…1 Beyond the effect of adversity on an individual’s SRSs, there is evidence that mothers’ experiences of stress during pregnancy can affect her developing child’s SRSs, including the autonomic nervous system (ANS). 24 ACEs also appear to have effects on the next generation, as preconception maternal early life adversity is associated with preterm birth and low birth weight, and maternal sexual abuse history independently predicts poorer birth outcomes. 5,6 Furthermore, maternal history of childhood abuse predicts hypothalamic–pituitary–adrenal (HPA) axis functioning in her offspring.…”
mentioning
confidence: 99%
“…Even though there was a break in between the previous tasks and the still‐face task, it is possible that infants might have carried over some distress to the still‐face procedure. Additionally, recent research has found that RSA levels can be considered as a biological sensitivity factor as RSA levels interact with children's social environment/maternal characteristics to predict children's subsequent outcome (Conradt, Measelle, & Ablow, ; Peltola et al, ). Therefore, to better understand the role of RSA levels play in children's adjustment, the caregiving environment/maternal characteristics may need to be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Children with certain profiles may be more influenced by negative aspects of the caregiving environment, and simultaneously, better able to benefit from supportive aspects of the caregiving environment. The differential susceptibility framework has been supported with behavioral (Belsky, Bakermans‐Kranenburg, & van Ijzendoorn, ), genetic (van Ijzendoorn & Bakermans‐Kranenburg, ), and biological (Wagner, Mills‐Koonce, Willoughby, & Cox, in press) markers, including RSA (Peltola et al, ). Housed within the autonomic nervous system (ANS), which functions to regulate unconscious biobehavioral response (Beauchaine, ), the parasympathetic nervous system promotes homeostasis and regulates response to stress (Beuchaine, ; Perry, Swingler, Calkins, & Bell, ; Porges, ).…”
Section: Introductionmentioning
confidence: 99%